The Impact of Social Intelligence and Sense of Humor on Entrepreneurial Intention: Evidence from Turkey - (:unkn) unknown (ACAD CONFERENCES LTD, 2009)
The main objective of this study is to investigate the relationship between social intelligence, sense of humor and entrepreneurial intention. In this study it is assumed that social intelligence is an important factor of an individual's entrepreneurial intention and the impact of social intelligence on entrepreneurial intention is stronger when social intelligence is supported by sense of humor. In literature, several factors that influence entrepreneurial intention have been noted. In simple terms, entrepreneurial intention is one's willingness in undertaking entrepreneurial activity, or in other words become self employed. The previous studies on entrepreneurial intention mostly covers the personality factors, behavioral approaches, demographics and contextual elements. There are also various studies and research on social intelligence and humor independently. Social intelligence is a widely researched area in terms of personality factors and traits. It is mostly related to successful outcomes of human behavior. Sense of humor and the role of humor in organizations are becoming increasingly popular among the scholars. However, to the knowledge of the authors, these three concepts have not been combined in literature. A survey was used as a research instrument and was applied to 236 newly graduated university students, in Istanbul, Turkey. Results show a significant relationship between social intelligence and entrepreneurial intention. The explanatory power of our model increases when social intelligence is accompanied by sense of humor. Therefore, it can be concluded that entrepreneurial intention of an individual increases when social intelligence is supported by sense of humor. Although entrepreneurial intention is a widely researched area, our knowledge about its determinants is still limited. In addition, in researching entrepreneurial intention determinants, this study aims represent a different perspective by combining two concepts, social intelligence and sense of humor, which are not widely used in the field. This study also provides evidence to entrepreneurial intention and entrepreneurship field from a different cultural and economical setting.
Keywords: Entrepreneurial intention; social intelligence; sense of humor